Prediksi Suku Bunga Acuan (BI Rate) Menggunakan Metode Adaptive Neuro Fuzzy Inference System (ANFIS) - Nur Adli Ari Darmawand; Dian Eka Ratnawati; Rizal Setya Perdana (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
BI Rate is the interest rate policy that reflects the monetary stance policy which set by Bank of Indonesia and announced to the public. BI Rate is used as the parameter of economic activity of a country. BI Rate will affect the turnover of bank financial flows, inflation, and currency movement. The ups and downs of BI Rate are highly important for investors and market participants to increase or decrease the amount of production and to increase or decrease existing investment. That's what makes the BI Rate prediction important. The predicted BI Rate is expected to help investors and market participants to determine long-term economic decisions. In this study used Adaptive Neuro Fuzzy Inference System method which is a combination of steepest descent and least square estimator (LSE) algorithm for training. Based on the test results, it produces the best RMSE value 0.0019165.The final result obtained is the predicted value of bi rate.